Breaking Barriers in Pharmacy-Based Asthma Care: Challenges and Pathways to Effective Asthma Management - Ahmad, Anza; Muzaffar, Sana; Hussain, Azzah Khadim; Latif, Faziyya; Shoaib, Quratulain; Gull, Zartasha; Khan, Saif Ullah; Yousaf, Ahmad Ibne; Yousaf, Ayesha Bint (Indus Journal of Bioscience Research, 2025)
Introduction: Asthma, chronic respiratory disease affecting many people worldwide and remains public healthcare concern. Many scientific developments over the last 20 years have enhanced our knowledge of asthma and our capacity to successfully cope with and regulate it Since therapy and accurate medication consumption can decrease signs of asthma and disease development, recent recommendations emphasize the need to educate patients to how to manage their own conditions. Objectives: To study the barriers in asthma management and gathering the data regarding percentage of pharmacists managing asthma patients. Pharmacists are chosen voluntarily. Method: We surveyed 234 pharmacists currently working in community and hospital pharmacies in Lahore. The study outcome was self-reported that pharmacists have enough confidence, skills and time to asthma counseling and monitoring. Potential barriers included that the patients do not have enough time about empathetic discussions and counseling and providers do not receive incentives for counseling. Result: Most pharmacists reported that they have enough time for counseling (41%) and have enough confidence and skills in asthma monitoring (45%) and check patients inhalation techniques (41%) but patients’ point of view is that counseling is not pharmacist’s job and don’t agree on empathetic discussion with pharmacist (36%). Conclusion: Pharmacists are skilled and active in asthma management, improving patient self-care and adherence to guidelines. However, challenges include patient reluctance and pharmacists’ lack of incentives and support for further education.